INTERNET ADDICTION AND ITS INFLUENCE ON SLEEP QUALITY AMONG THE MEDICAL STUDENTS - Padmavathy KM; Hakim AR; Kalisyah A; Yuhanis Y; Irfan ZA; Luqman R; Arif Z; Rohith SS (Asian Journal of Medicine & Health Sciences, 2020)
Background: Sleep is of physiological importance for quality life and health. The extensive use of the internet leads to a state of addiction gradually among young people globally. Addiction may comprehend to be a cause for psychological issues by changing lifestyle habits. This study aimed to understand the influence of internet addiction on sleep quality among medical students in Malaysia. Methods: This observational cross-sectional study involved 120 consenting medical students. The participants provided demographic details and answered two validated questionnaires of PSQI (Pittsburgh Sleep Quality Index) for rating the sleep quality and Internet Addiction Test (IAT) for the level of internet use. The statistical analysis was done by using SPSS, version 22. Results: The medical students’ scores established that the internet addiction was average level while the sleep quality was affected. The correlation between sleep quality and internet addiction showed a weak positive association. IAT scores and PSQI Global scores of poor sleep quality (scores more than five) had a statistically significant (p<0.05) correlation. Conclusion: Participants had complete control of their internet use, showed an average level of internet addiction, but sleep quality was affected considerably with a positive association.